Targeting the LPS-STING axis: neomycin restores STING-mediated anti-tumor immune suppression and inhibits tumor growth - Fan, Hong; Fu, Dongjie; Tian, Mingfu; Li, Zhiqiang; Liu, Siyu; Ye, Chenglin; Wu, Kailang; Zhu, Chengliang (Frontiers in Immunology, 2025)
IntroductionThe interplay between microbial metabolites and host immunity within the tumor microenvironment (TME) critically modulates anti-tumor immune responses. The role of Gram-negative bacteria and their cell wall component lipopolysaccharide (LPS) in this context warrants further investigation.MethodsWe assessed the impact of low-dose LPS pretreatment on macrophage function by measuring type I interferon (IFN-β) secretion in response to tumor cell debris. Mechanistic insights were gained by analyzing endogenous signaling pathways in macrophages. The therapeutic potential of targeting LPS was evaluated in melanoma-bearing mice treated with neomycin, alone or in combination with STING agonists.ResultsLow-dose LPS pretreatment significantly suppressed IFN-β secretion by macrophages, indicating LPS-mediated immunosuppression. Mechanistically, LPS disrupted endogenous signaling pathways, blunting the ability of macrophages to sense tumor-derived damage signals. In vivo, neomycin treatment markedly inhibited melanoma growth and synergized with STING agonists.DiscussionOur findings demonstrate that elevated LPS in the TME inhibits anti-tumor innate immunity by impairing macrophage function. The combination of LPS modulation via neomycin with innate immune activation via STING agonists presents a potential strategy to enhance tumor immunotherapy.